ACL microtrauma: healing through nutrition, modified sports training, and increased recovery time - J. Nyland; B. Pyle; R. Krupp; G. Kittle; J. Richards; J. Brey (Journal of Experimental Orthopaedics)
Abstract Purpose Sports injuries among youth and adolescent athletes are a growing concern, particularly at the knee. Based on our current understanding of microtrauma and anterior cruciate ligament (ACL) healing characteristics, this clinical commentary describes a comprehensive plan to better manage ACL microtrauma and mitigate the likelihood of progression to a non‐contact macrotraumatic ACL rupture. Methods Medical literature related to non‐contact ACL injuries among youth and adolescent athletes, collagen and ACL extracellular matrix metabolism, ACL microtrauma and sudden failure, and concerns related to current sports training were reviewed and synthesized into a comprehensive intervention plan. Results With consideration for biopsychosocial model health factors, proper nutrition and modified sports training with increased recovery time, a comprehensive primary ACL injury prevention plan is described for the purpose of better managing ACL microtrauma, thereby reducing the incidence of non‐contact macrotraumatic ACL rupture among youth and adolescent athletes. Conclusion Preventing non‐contact ACL injuries may require greater consideration for reducing accumulated ACL microtrauma. Proper nutrition including glycine‐rich collagen peptides, or gelatin‐vitamin C supplementation in combination with healthy sleep, and adjusted sports training periodization with increased recovery time may improve ACL extracellular matrix collagen deposition homeostasis, decreasing sudden non‐contact ACL rupture incidence likelihood in youth and adolescent athletes. Successful implementation will require compliance from athletes, parents, coaches, the sports medicine healthcare team, and event organizers. Studies are needed to confirm the efficacy of these concepts. Level of evidence V